CULTURE OF CORRUPTION AS A KEY ISSUE IN ANTI-CORRUPTION METHODOLOGY AND POLICIES (ON EXAMPLES OF ITALY AND ARMENIA) - Edgar Kalantaryan (Banber Erevani Hamalsarani. Sots'iologia)
The aim of this article is to examine the presence of a culture of corruption in public administration systems, assess its negative impact on governance, and evaluate anti-corruption methodologies for enhancing governmental effectiveness. In this context, we explore various manifestations of corruption in public organizations and analyze international experiences - particularly the case of Italy - where we conduct a comprehensive review of its anti-corruption policies and highlight their significance in fostering an effective governance system. The more we know about the causes of corruption, the better we can decide which policy instruments to use to combat corruption. Corruption is a phenomenon that gains public visibility in democratic regimes because in such regimes there are freedom of press, freedom of expression, free party organizations, and opposition to the governments on duty. However, although democracy has the merit of not hiding corruption, not confronting and not containing acts that are harmful to the public interests can be lethal to democracy itself by generating autocratic governments that place themselves above political institutions (Ribeiro, 2000). The study examines the framework and methodologies of anti-corruption policies in the Republic of Armenia, comparing them with the experience of Italy. The theoretical foundation for addressing the issues discussed in this research is based on classical and modern theories of public administration, political science, and sociology. The study employs analytical, comparative, and systemic methods. Italy - being surrounded by European countries, possessing a more institutionalized governance system, and having a more democratic and socially mature society - finds itself in a relatively advantageous position in combating corruption compared to Armenia. Nonetheless, Italy still faces persistent corruption-related challenges. In contrast, Armenia’s situation is shaped by its Soviet legacy, the Karabakh (Artsakh) conflict, and the inefficiencies in governance since independence, all of which have contributed to the persistence of a culture of corruption. Despite significant legislative advancements in recent years, systemic inefficiencies remain. Addressing corruption requires time, skilled professionals, strong managerial will, and other critical factors. International experience in managing state institutions plays a crucial role in shaping Armenia’s anti-corruption efforts. With the purpose of providing better conditions for the adequate understanding of corruption, this article seeks to systematize some of the main theoretical reflections on the subject, highlighting attempts to conceptualize and classify it, as well as some of the approaches developed with the aim of understanding its causes and devising strategies for its control.